2015
DOI: 10.5812/ijp.2436
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Acceptance and Commitment Therapy for Depression, Psychological Well-Being and Feeling of Guilt in 7 - 15 Years Old Diabetic Children

Abstract: Background:Diabetes imposes restrictions on physical, emotional, and social functioning of children and adolescents.Objectives:The aim of this study was to determine effectiveness of acceptance and commitment therapy (ACT) for depression, psychological well-being and feeling of guilt in 7 - 15 years old diabetic children.Patients and Methods:This was a clinical trial with pre-test and post-test design with control group. The study population consisted of 34 participants selected using convenient sampling out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…One study found significant improvement in psychological wellbeing [66]. Of the two that measured depression, one found a significant reduction post-intervention [58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found significant improvement in psychological wellbeing [66]. Of the two that measured depression, one found a significant reduction post-intervention [58].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on ACT interventions examined well-being, depression, anxiety, and stress. One study found significant improvement in psychological wellbeing [66]. Of the two that measured depression, one found a significant reduction post-intervention [58].…”
Section: Resultsmentioning
confidence: 99%
“…Guilt feeling is frequently expressed by adolescents with diabetes and psychological therapy can be effective in its management [ 30 ]. The guilt feeling in adolescents with diabetes might arise from their beliefs that they can be a “burden” on their family.…”
Section: Parental Psychopathologymentioning
confidence: 99%
“…Four studies were randomized controlled trials [37,[51][52][53], three were quasi-experimental pre-post designs with random assignment [54][55][56], and three were pre-post with control groups and random assignment [57][58][59]. Five studies were conducted in Iran [54][55][56][57][58], two in Australia [51,60], one in Sweden and Australia (one article with a study cohort in each country) [52], and one in Hong Kong [53] and one in the USA [59]. ACT was administered via weekly sessions (average of 8 sessions) with a trained psychologist, or a trained nurse supervised by a psychologist.…”
Section: Study Characteristicsmentioning
confidence: 99%